Hubungan Pengetahuan, Peran Kader Jumantik dan Penyuluhan dengan Upaya Pencegahan Penyakit Demam Berdarah Dengue - Yulyanti, Revi; Heryanto, Eko; Lilia, Deli (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
The study addresses the escalating global health concern of Dengue Hemorrhagic Fever (DHF), particularly in Indonesia, where mortality rates decreased significantly from 41.3% in 1968 to 0.87% in 2010. Despite this achievement, morbidity rates remain high, emphasizing the need for effective prevention strategies. The study, conducted in Air Paoh Village, OKU Regency, aims to explore the relationship between knowledge, the role of jumantik cadres, counseling, and family head actions in DHF prevention. Utilizing a Cross-Sectional research design, the study included 93 heads of families from a total population of 2,553. Univariate analysis revealed that 72% of respondents demonstrated good efforts in dengue prevention, with 60.2% possessing adequate knowledge. Additionally, 47.3% acknowledged the role of jumantik cadres, while 53.8% attended counseling sessions. Bivariate analysis using the chi-square test indicated significant associations. Knowledge had a p-value of 0.000, the role of jumantik cadres showed a p-value of 0.026, and counseling exhibited a p-value of 0.001. These results suggest a meaningful correlation between knowledge, the involvement of jumantik cadres, counseling attendance, and the actions taken by family heads in preventing DHF in Air Paoh Village.The study's implications highlight the importance of targeted education, active involvement of community cadres, and enhanced counseling programs to reinforce preventive actions. The findings contribute valuable insights for public health strategies, emphasizing the significance of a multifaceted approach to combat the growing prevalence of DHF in the community.